Luminescence Properties of Fe2+:ZnSe Single Crystals Grown via a Traveling Heater Method - Weina Nan; Da Yang; Boru Zhou; Liang Zhang; Jing Xiao; Hongwei Yu; Zhanggui Hu; Yicheng Wu (Crystals, 2023)
The luminescence properties of iron-doped ZnSe (Fe2+:ZnSe) single crystals grown via a traveling heater method have been studied via photoluminescence (PL). Nine emission bands were identified in the PL spectra of Fe2+:ZnSe single crystals and their origins were also discussed. The near-infrared emission bands seen at 820 nm and 978 nm can be attributed to the emission bands formed by the background Fe or other impurity-related defect complexes in Fe2+:ZnSe single crystals, rather than by doped transition-metal-related defects. With the increase in temperature, the PL intensity increased slightly and reached a maximum near room temperature for bound excitons (430–490 nm), but the PL intensity decreased significantly for impurity-defect emission bands (500–720 nm), indicating the occurrence of a thermal quenching effect. The excitation wavelength-dependent PL spectra showed that PL intensity first increased and then decreased with an increase in the excitation wavelengths, and the maximum PL intensity of the bound excitons was obtained at 364 nm. In addition, the X-ray photoelectron spectroscopy (XPS) results showed that both bivalent and trivalent iron ions were found, but bivalence was the dominant charge state for iron atoms in the iron-doped ZnSe single crystals, meaning that they are suitable for developing mid-infrared gain medium applications.